Przeprowadzenie postępowania dowodowego podczas usprawiedliwionej nieobecności oskarżonego lub jego obrońcy na rozprawie - Żbikowska, Małgorzata (Wydawnictwo Uniwersytetu Wrocławskiego, 2020)
The subject of study is an analysis of the content of art. 378a of the Code of Criminal Procedure, added to the Code of Criminal Procedure on October 5, 2019. The legal provision under examination allows evidence to be taken in the absence of the accused or his defense counsel, even if it is justified by the absence. The author considers the legitimacy of introducing art. 378a of the Code of Criminal Procedure, and also takes into account the correctness of its construction. As a result of these considerations, he finds many flaws in the applicable legal regulations and tries to mitigate the negative effects of the introduction to the Polish legal system of the possibility of taking evidence during a duly substantiated absence of the accused or his defender at the trial.
Keywords: absence of the accused at the trial; evidence proceedings in the absence of the accused; evidence proceedings; right of defense; accused